Cellular zirconia ceramics processed by direct emulsification. Issue 5 (May 2020) - Ivanova, Yu. A.; Freitas, C.; Lopes, D.V.; Kovalevsky, A.V.; Frade, J.R.
Abstract: Highly porous zirconia ceramics for prospective use as separators in alkaline electrolysis cells have been processed by emulsification of paraffin in concentrated zirconia suspensions. Effects of processing parameters on porosity, cell size distribution, and pore interconnectivity are studied through Taguchi statistical design. The porosity of zirconia ceramics has shown a strong correlation with paraffin-to-suspension ratio employed in emulsification. High paraffin-to-suspension ratios combined with high gelatin content in the emulsion are beneficial for creating highly porous cellular materials with interconnected cell sizes. The attained microstructural features allow high percolation of ionic species in these highly porous ceramics after impregnation with aqueous electrolytes, facilitating charge transport within the liquid medium inside the ceramic bodies, as required for lower ohmic losses. This work provides guidelines for developing efficient ceramic separators for future use in alkaline electrolysis cells and other applications requiring thermally and chemically-stable ceramics with high and well-interconnected porosity.